Preparation of ZnO@ZnS core-shell nanorod arrays with enhanced photocurrent for removal of methylene blue dyes in wastewater - Yu-Zhe Wu; Wenjea J. Tseng (Open Ceramics)
This study synthesized core-shell zinc oxide@zinc sulfide nanorod arrays (ZnO@ZnS NRAs) using a hydrothermal process in a thioacetamide solution, with sulfidation temperatures ranging from 60 to 100 °C. An increased sulfidation temperature resulted in a higher ZnS fraction within the ZnO@ZnS NRAs. ZnO@ZnS NRAs prepared at 70 °C, with a ZnS ratio of approximately 70:30 by weight, exhibited the highest photocurrent density of 0.22 mA·cm−2 under xenon-lamp irradiation at a bias voltage of 1.5 V (vs. Ag/AgCl). X-ray photoelectron spectroscopy, photoluminescence, and electron paramagnetic resonance analyses confirmed the presence of vacancy defects, which are believed to promote the separation of photoinduced charge carriers, thereby enhancing carrier density. The increased photocurrent facilitated the efficient photodegradation of methylene blue dye in aqueous solutions, following Langmuir-Hinshelwood kinetics for heterogeneous catalysis. The first-order rate constant for the ZnO@ZnS NRAs treated at 70 °C was double that of the pristine ZnO counterpart. The band alignment at the ZnO-ZnS interface, combined with effective electron-hole separation, contributes to the enhanced photoelectrochemical and photocatalytic activity of the ZnO@ZnS NRAs.